Much ado, little afoot? How the Nordics approach Taiwan - Andreas Bøje Forsby (Danish Institute for International Studies (DIIS), 2024)
As the Taiwan issue has become increasingly sensitive in the past several years, the Nordic governments are struggling to strike the right balance amid widespread calls for stepping up the support for Taiwan and deepening concerns about violating China's notorious core interests. Against the wider backdrop of current European engagement with/detachment from Taiwan, this report provides an in-depth empirical mapping and comparison of how the five Nordic countries - Denmark, Finland, Iceland, Norway and Sweden - are handling their unofficial political relations with Taiwan. Focusing on each country's "One China" policy, its practical management of bilateral relations and its Taiwan-related parliamentarian activism, the report finds that the Nordics can be divided into a set of "isolationist" countries (Iceland and Norway) with virtually no direct channels of institutionalised bilateral interaction and a group of "commercial pragmatists" (Denmark, Finland and Sweden) who operate trade offices in Taipei alongside Taiwanese representative offices in their own capitals. The report shows that all the Nordic governments have recently adopted a very cautious approach in the face of Beijing's increasingly assertive imposition of its "One China" principle. Indeed, the growing willingness of parliamentarians in some of the Nordic countries (notably Sweden) to put Taiwan on their political agenda has been to little avail as long as the Nordic governments continue to ignore or curtail Taiwan-related queries and proposals. Until the Nordic governments clarify their position - ultimately by rejecting (or endorsing) the "One China" principle - the state of Nordic-Taiwan relations will remain fragile and contested.
Keywords: 300